Search and Rescue Capacity Building of Nepal’s Security Forces for Effective Response - K.C., Jeeven (Journal of APF Command and Staff College, 2022)
Capacity building encompasses the training, knowledge, skills, abilities, processes, and resources. The present paper highlights Nepal’s security forces integral role in disaster response and its need of the capacity building in search and rescue. Responding to disasters is a special task that demands a high level of training, knowledge, skills, and types of tool, equipment, and accessories. During the study, trained manpower for search and rescue within the Nepali Army, Nepal Police, and Armed Police Force, Nepal, and their capabilities and challenges were analyzed. The study suggests need for investment in capacity building of security forces towards highly-trained manpower in search and rescue as per the international standard. Well-prepared human resource in sufficient number is key to effective response and integrated effort with sound coordination mechanism always gives the net positive results.